Genetic diversity of thermotolerant Campylobacter spp. isolates from different stages of the poultry meat supply chain in Argentina = Diversidad genética de Campylobacter spp. termotolerantes aislados de diferentes etapas de la cadena cárnica aviar en Argentina - Zbrun, María Virginia; Romero Scharpen, Analía; Olivero, Carolina Raquel; Zimmermann, Jorge Alberto; Rossler, Eugenia; Soto, Lorena Paola; Astesana, Diego Martín; Blajman, Jesica E.; Berisvil, Ayelén Patricia; Frizzo, Laureano Sebastian; Signorini, Marcelo (2018)
The objective of this study was to investigate a clonal relationship among thermotolerant Campylobacter spp. isolates from different stages of the poultry meat supply chain in Argentina. A total of 128 thermotolerant Campylobacter spp. (89 C. jejuni and 39 C. coli) isolates from six poultry meat chains were examined. These isolates were from: a) hens from breeder flocks, b) chickens on the farm (at ages 1 wk and 5 wk), c) chicken carcasses in the slaughterhouse, and d) chicken carcasses in the retail market. Chickens sampled along each food chain were from the same batch. Campylobacter spp. isolates were analyzed using pulsed-field gel electrophoresis to compare different profiles according to the source. Clustering of C. jejuni isolates resulted in 17 profiles, with four predominant genotypes and many small profiles with just a few isolates or unique patterns, showing a very high degree of heterogeneity among the C. jejuni isolates. Some clusters included isolates from different stages within the same chain, which would indicate a spread of strains along the same poultry meat chain. Moreover, twenty-two strains of C. coli clustered in seven groups and the remaining 17 isolates exhibited unique profiles. Evidence for transmission of thermotolerant Campylobacter spp. through the food chain and cross contamination in the slaughterhouses were obtained. This collective evidence should be considered as the scientific basis to implement risk management measures to protect the public health.